A REVIEW ON THE PREVALENCE OF HYPERTENSION IN SIDE-LINED POPULATIONS; SLUM DWELLERS, SHIFT JOB WORKERS AND OCCUPATIONAL NOISE AFFECTED WORKERS: ATTRIBUTABLE TO LIFESTYLE AND ENVIRONMENTAL FACTOR - Yadav, Sanjeev; Saraswat, Nikita; Saini, Aryendu Kumar; Wal, Pranay (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Hypertension is a condition that is characterized by the persistent raised blood pressure. It is not seen as a disease rather as a major risk factor that is solely responsible for different types of cardiovascular diseases such as heart failure, ischemic heart disease, and left ventricular hypertrophy. Although this condition cannot be cured, hypertension can be managed and prevented by adopting a healthy lifestyle that encompasses factors such as diet, physical exercise, reduced alcohol consumption, moderate sodium and potassium intake, and psychological factors. Apart from these, environmental factor like noise has also proved to be associated with the high blood pressure. Different prevalence studies have been conducted to find out the relationship between high blood pressure and different lifestyle factors. This article aims to review and emphasize the prevalence of high blood pressure in slum dwellers and at-risk workers who are shift job workers and occupational noise affected workers. Different research articles pertaining to different authors and countries have been reviewed to portray the concern of this condition. There is the need for proper recognition to these folks of people who are exposed to the precarious and high-risk style of living in the slum dwellers, shift job workers, and occupational noise affected workers. The distress in the physiological functioning of the body leading to hypertension has been found in the slum dwellers and at-risk workers; shift job workers and occupational noise affected workers that are again attributable to aforementioned lifestyle and environmental factor. The proper management of hypertension is extremely required to safeguard these unacknowledged groups of people.